ACUTE SYMPTOMS FOLLOWING WORK WITH PESTICIDES - Solomon, Christine (2007)
OBJECTIVES: To explore the frequency, nature and determinants of acute symptoms following work with pesticides. METHODS: As part of a postal survey of men born during 1933-77 and resident in three rural areas of England and Wales, data were obtained on demographic variables; occupational use of five categories of pesticide; whether any of 12 specified symptoms had ever occurred within 48 hours of using such pesticides; and tendency to somatise (graded to four levels). Associations of pesticide-related symptoms with risk factors were assessed by modified Cox regression, and the timing of first recalled symptoms in relation to calendar period and years of work with pesticides by Poisson regression. RESULTS: Of 10,765 responders (response rate = 31%), 4,108 had at some time used pesticides occupationally, including 935 (23%) who reported symptoms following such work on at least one occasion. In two areas, acute symptoms were most frequent following use of sheep dip (29% and 32% of users), but in the third area, sheep dip was less often associated with symptoms (13% of users) than other insecticides (15% of users). The relative frequency of symptoms was similar for all five categories of pesticide, and there was no evidence that flu-like symptoms clustered unusually among users of sheep dip, as has previously been postulated. Multiple pesticide-related symptoms and symptoms in relation to multiple categories of pesticide were both much more common than would have been expected if individual symptoms were statistically independent. Risk of acute pesticide-related symptoms increased with somatising tendency (prevalence ratio for highest v lowest category 2.4, 95%CI 2.0-3.0), and was higher in men who had used pesticides most often, and who had handled concentrate. First onset of symptoms was more common in the first year of pesticide use (incidence rate ratio 4.5, 95%CI 3.5-6.8 in comparison with first use >15 years earlier), and peaked in the late 1980s. However, this peak of incidence disappeared when men who had worked with sheep dip were excluded from the analysis. CONCLUSION: Our findings indicate that acute symptoms are common following work with pesticides, but suggest that in many cases the illness may arise through psychological rather than toxic mechanisms.